2019
DOI: 10.1002/kjm2.12077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UDP‐glucuronosyltransferase 1A1 activity on risk for developing Gilbert's syndrome

Abstract: Variations at the six nucleotides −3279 (T > G), −53 (A[TA]6TAA > A[TA]7TAA), 211 (G > A), 686 (C > A), 1091 (C > T), and 1456 (T > G) in the UDP‐glucuronosyltransferase 1A1 (UGT1A1) gene were determined in 178 Taiwanese patients with Gilbert's syndrome and in 200 healthy adults. Every subject was classified as a genotype depending on variation status of the six nucleotides in the UGT1A1 gene. The UGT1A1 activity for each genotype was calculated and then those genotypes were divided into 10 subgroups (Q1~Q10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 40 publications
0
46
0
3
Order By: Relevance
“…The five SNPs at nucleotides À53, 211, 686, 1091 and 1456 of the UGT1A1 gene were determined by means of polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), as previously described. 11 The DNAs of the five known variants in the UGT1A1 gene, which had been found in Taiwanese and identified by DNA sequencing methods, 11 were run as positive controls in each performance of genotyping assays.…”
Section: Determinations Of Snps and Ugt1a1 Enzyme Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…The five SNPs at nucleotides À53, 211, 686, 1091 and 1456 of the UGT1A1 gene were determined by means of polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), as previously described. 11 The DNAs of the five known variants in the UGT1A1 gene, which had been found in Taiwanese and identified by DNA sequencing methods, 11 were run as positive controls in each performance of genotyping assays.…”
Section: Determinations Of Snps and Ugt1a1 Enzyme Activitymentioning
confidence: 99%
“…The enzyme activity values for 686CA, À53 A(TA) 7 TAA/A(TA) 7 TAA, 1091 TT, 211 GA, 211AA and 1456 GG variants were obtained from previously published studies 4,8,13,14 as shown in Table 1, while those for 686AA, À53 A(TA) 6 TAA/A(TA) 7 TAA, 1091CT and 1456 TG variants were estimated by calculation {UGT1A1 activity for 686AA Z [(activity for 686CA) 2 (square)], while activity for A(TA) 6 TAA/ A(TA) 7 TAA Z [activity for A(TA) 7 TAA/A(TA) 7 TAA] 1/2 and so on}. 11 For subjects carrying multiple SNPs in the UGT1A1 gene, estimated UGT1A1 enzyme-activities were obtained by calculations. 11 However, for subjects carrying two SNPs in close linkage, e.g., 686A/e53 A(TA) 7 TAA, the UGT1A1 enzyme activity of the SNP with lower activity between those two SNPs was estimated, avoiding over-or underestimation.…”
Section: Determinations Of Snps and Ugt1a1 Enzyme Activitymentioning
confidence: 99%
See 3 more Smart Citations